2021
DOI: 10.1007/s00033-021-01592-w
|View full text |Cite
|
Sign up to set email alerts
|

The onset of thermal convection in anisotropic and rotating bidisperse porous media

Abstract: The onset of thermal convection in anisotropic rotating bidisperse porous media is investigated. The optimal result concerning the coincidence between linear instability and nonlinear stability thresholds with respect the $$L^2$$ L 2 -norm is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Anisotropic effects upon thermal convection in saturated porous media have been the subject of many recent investigations, see e.g. Capone et al [31][32][33][34][35], Hemanthkumar et al [36][37][38]. In particular the ramifications of anisotropy in porous media have proved of interest in the application to healthcare materials and in human tissues, see Fang et al [39], Mirbod et al [40].…”
Section: Effects On Penetrative Convectionmentioning
confidence: 99%
“…Anisotropic effects upon thermal convection in saturated porous media have been the subject of many recent investigations, see e.g. Capone et al [31][32][33][34][35], Hemanthkumar et al [36][37][38]. In particular the ramifications of anisotropy in porous media have proved of interest in the application to healthcare materials and in human tissues, see Fang et al [39], Mirbod et al [40].…”
Section: Effects On Penetrative Convectionmentioning
confidence: 99%
“…Accounting for the discussion made in [26], in this paper, we focus the attention on a single‐temperature bi‐disperse porous medium, that is, T=Tf=Tp$$ T={T}^f={T}^p $$. Bi‐disperse convection has been widely analyze under various physical assumptions, for instance: In [27, 28], double diffusive bi‐dispersive convection was investigated, and papers [29–33] analyzed the onset of convection in anisotropic bi‐disperse porous media. The novelty of this paper is the investigation of penetrative convection in bi‐disperse porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, BDPM can be seen as a permeable material that has undergone the creation of tunnels or cracks, with the terms “solid phase” and “fracture phase” replacing “ p ‐phase” and “ f ‐phase” in the current model. Convection in BDPM has gained increasing interest due to its practical applications, such as utilizing BDPM‐like absorbent and capillary wicks in heat pipes to enhance heat transfer efficiency 3–6 . Moreover, it has been observed that BDPM surpasses conventional porous media in addressing thermal insulation and system cooling challenges to a significant extent 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Convection in BDPM has gained increasing interest due to its practical applications, such as utilizing BDPM-like absorbent and capillary wicks in heat pipes to enhance heat transfer efficiency. [3][4][5][6] Moreover, it has been observed that BDPM surpasses conventional porous media in addressing thermal insulation and system cooling challenges to a significant extent. 7,8 The research on heat convection in BDPM was initially introduced by Nield et al [9][10][11][12] Their work specifically focused on forced convection in BDPM, analyzing uniform heat flux and constant wall temperature in a channel.…”
mentioning
confidence: 99%